Modelo matemático de otimização para a alocação de chaves seccionadoras e ramais de interconexão em sistemas de distribuição de energia elétrica - Conceição, Katiani Pereira da (2014)
The development of a mathematical optimization model for the allocation of switching devices and interconnecting branches in electric power distribution systems is presented. This model aims to minimize the cost of load unserved energy and investment costs. The main constraints are continuity indicators, like DEC and FEC and technical constraints from the power flow of the system. The model is a mixed integer nonlinear programming (MINLP) which proposes the building of new interconnection lines between the main branch and lateral extensions of the same feeder. The objectives of this model are to improve system reliability and minimize energy costs, the construction of the Pareto curve by varying weighting factors contained in the objective function is presented in order to find a set of solutions to be presented to the decision maker of a distribution utility. To prove the behavior of the model, a genetic algorithm was used as solution technique in several test systems.